2019
DOI: 10.1007/s13762-019-02429-w
|View full text |Cite
|
Sign up to set email alerts
|

Human health risk assessment of arsenic downstream of a steel plant in Isfahan, Iran: a case study

Abstract: This paper presents impacts of arsenic due to a steel plant operation on an agricultural and residential area. A spatial dispersion modeling of arsenic in fugitive particulates was implemented using AERMOD as a tool for analyzing the impacts of steel complex emissions in southwest of Isfahan, Iran, based on US Environmental Protection Agency (EPA) Guidelines. Evaluating the model, EPA's speciate database was used to determine the proportion of the steel plant in air pollution among other sources in the region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Tavakoli et al reported that the carcinogenic risk was between 2.42E-5 (minimum risk) and 1.13E-3 (maximum risk) for smokers, as well as 2.86E-6 (minimum risk) and 1.13E-3 (maximum risk) for nonsmokers in 2016. 45 Maleki et al reported that carcinogenic risk was between 3.78E−4 and 2.65E−3 and from 5.67E−4 to 3.97E−3 for warm and cold seasons, respectively, from 2018 to 2019. 43 Given that the AQCC reports the mean concentration for the whole city, the difference in results is to be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Tavakoli et al reported that the carcinogenic risk was between 2.42E-5 (minimum risk) and 1.13E-3 (maximum risk) for smokers, as well as 2.86E-6 (minimum risk) and 1.13E-3 (maximum risk) for nonsmokers in 2016. 45 Maleki et al reported that carcinogenic risk was between 3.78E−4 and 2.65E−3 and from 5.67E−4 to 3.97E−3 for warm and cold seasons, respectively, from 2018 to 2019. 43 Given that the AQCC reports the mean concentration for the whole city, the difference in results is to be expected.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of researches indicated that it has harmful effects on kidneys, skin and bones [35]. The rate of exposure to these carcinogenic elements is higher in the case of inhalation than in other methods of exposure such as ingestion or through the skin [36]. The lifetime cancer risk (LCR) is calculated for arsenic and chromium to identify the health risks for them in the long term and in the short term as they are carcino-genic elements [5,20], where LCR was calculated for the mentioned elements during a year and within one hour.…”
Section: ) Studying the Health Risks For Carcinogenic Elementsmentioning
confidence: 99%